Relationship between serial serum neutrophil-lymphocyte ratio, cardiovascular mortality, and all-cause mortality in Chinese peritoneal dialysis patients - Lik Fung Sam Lau; Jack K.C. Ng; Winston W.S. Fung; Gordon C.K. Chan; Phyllis M.S. Cheng; Kai-Ming Chow; Chi-Bon LEUNG; Philip Kam-To Li; Cheuk-Chun Szeto (Karger Publishers, 2023)
Background It is believed that the excessive cardiovascular (CV) burden of patients on peritoneal dialysis (PD) is closely associated with chronic inflammation. Neutrophil-lymphocyte ratio (NLR) is an inflammatory marker that was shown to correlate with CV outcomes. However, little is known about the significance of serial monitoring of serum NLR. We aimed to determine the prognostic value of serial NLR on all-cause mortality and CV mortality in PD patients. Methods Serial measurement of NLR was obtained from 225 incident PD patients in a single center, with each measurement one year apart. Patients were divided into two groups ('high' versus 'low') by the median value of NLR. The primary and secondary outcome measure was all-cause and CV mortality respectively. Results After a median of follow up for 43.9 months, patients with lower baseline NLR demonstrated a higher survival rate (p=0.01). Patients with persistently high NLR values on serial measurement had the lowest survival rate (p=0.03). Multivariate Cox regression showed that this group of patients had significantly higher all-cause mortality (HR 1.74, 95%CI 1.09 to 2.79, p=0.02). However, the NLR failed to demonstrate a statistically significant relationship with CV mortality. Conclusions While baseline NLR was an independent predictor of all-cause mortality in PD patients, persistent elevation in NLR appeared to further amplify the risk. Regular monitoring of serial serum NLR may enable early identification of patients who are at risk of adverse outcome.